On the glacial and interglacial thermohaline circulation and the associated transports of heat and freshwater - M. Ballarotta; S. Falahat; L. Brodeau; K. Döös (Ocean Science, 2014)
The thermohaline circulation (THC) and the oceanic heat and freshwater transports are essential for understanding the global climate system. Streamfunctions are widely used in oceanography to represent the THC and estimate the transport of heat and freshwater. In the present study, the regional and global changes of the THC, the transports of heat and freshwater and the timescale of the circulation between the Last Glacial Maximum (LGM, ≈ 21 kyr ago) and the present-day climate are explored using an Ocean General Circulation Model and streamfunctions projected in various coordinate systems. We found that the LGM tropical circulation is about 10% stronger than under modern conditions due to stronger wind stress. Consequently, the maximum tropical transport of heat is about 20% larger during the LGM. In the North Atlantic basin, the large sea-ice extent during the LGM constrains the Gulf Stream to propagate in a more zonal direction, reducing the transport of heat towards high latitudes by almost 50% and reorganising the freshwater transport. The strength of the Atlantic Meridional Overturning Circulation depends strongly on the coordinate system. It varies between 9 and 16 Sv during the LGM, and between 12 to 19 Sv for the present day. Similar to paleo-proxy reconstructions, a large intrusion of saline Antarctic Bottom Water takes place into the Northern Hemisphere basins and squeezes most of the Conveyor Belt circulation into a shallower part of the ocean. These different haline regimes between the glacial and interglacial period are illustrated by the streamfunctions in latitude–salinity coordinates and thermohaline coordinates. From these diagnostics, we found that the LGM Conveyor Belt circulation is driven by an enhanced salinity contrast between the Atlantic and the Pacific basin. The LGM abyssal circulation lifts and makes the Conveyor Belt cell deviate from the abyssal region, resulting in a ventilated upper layer above a deep stagnant layer, and an Atlantic circulation more isolated from the Pacific. An ...